Plasticity in the binocular correspondence of striate cortical receptive fields in kittens. - Dürsteler, M R (1983)
The influence of visual experience on the correspondence in position and orientation of receptive fields in the two eyes of cortical neurones was studied. Kittens were reared viewing the environment through lenses that magnified the image by 9% in one direction (meridional size lenses) with axes of magnification oriented 45 degrees left and right of vertical for the two eyes. The unequal deformations in the two eyes produced gradients of position disparity and systematic variation of orientation disparity which could not be influenced by eye movements. Two types of arrangement of the lenses, producing opposite disparities, were used; each was worn by two kittens. The receptive fields of cortical neurones were studied in the four kittens aged 3-4 months. In the binocular cells, the positions of the response fields were plotted, and the preferred orientations determined, using automatic stimulus variation, quantitative analysis, and eye-drift correction. By means of regression analysis, the degree of 'interocular deformation' was assessed; a coefficient D was derived from the positions, an angle beta from the orientations. D specified the position incongruity as a fraction of retinal eccentricity, beta the difference between the orientation incongruities of cells with near-vertical and near-horizontal receptive fields. Both D and beta were found to be of opposite signs in the two groups of kittens, as predicted by the optical effects of the lenses. The difference in D between the groups was 0.197 (predicted: 0.172); the difference in beta was 17.0 degrees (predicted: 18.9 degrees). Thus, the difference in visual environment had been completely compensated by adjustments in the positions as well as the orientations of the receptive fields. Since D and beta are independent of the alignment of the eyes, the differences between the groups reflected different functional connexions at the cortical level. Possible advantages of plasticity for the development of binocular vision are discussed. It is argued that the plasticity demonstrated here reflects a more general property of cortical receptive fields.